Hubungan Caring Keluarga Terhadap Kepatuhan Diet dan Minum Obat Pada Pasien Hipertensi di Puskesmas Sungai Tabuk 1: The Relationship Between Family Caring and Compliance with Diet and Medication in Hypertension Patients at Sungai Tabuk 1 Public Health Center - Sa’diah, Halimatus; Rian Tasalim; Subhannur Rahman (LPPM STIKES Guna Bangsa, 2025)
Hypertension is a health condition characterized by elevated blood pressure, often unnoticed by the individuals affected. Due to the absence of typical symptoms, hypertension is often referred to as the